Nursing management for hemodialysis patients in the Intensive Care Unit: integrative review (Research, Society and Development, 2022)
Objective: To identify, in the scientific evidence, the care of nurses in the intensive care unit for the management of patients undergoing hemodialysis. Methodology: This is an integrative review that took place between February and May 2022, through the Scientific Electronic Library Online (SciELO), Virtual Health Library (BVS), Health Sciences of Latin America and the Caribbean databases. (LILACS) and National Library of Medicine (PUBMED/MEDLINE), with the health sciences descriptors “nursing care/Nurse Care”, “hemodialysis/Renal dialysis”, “acute kidney injury/ Acute Kidney Injury” and “care unit”. intensive care/ Intensive Care Units”. Results: The sample consisted of 10 articles from different databases that involved the following themes: Pre-hemodialysis, Intra-dialysis and post-hemodialysis Nursing Care. Conclusion: The present study made it possible to identify nursing care for the management of hemodialysis patients in the Intensive Care Unit, such care guarantees the professional nurse autonomy, decision-making and provision of safe assistance in the face of hemodialysis management. There is a need for more scientific evidence that addresses the issue of the hemodialysis process in the pre, intra and post hemodialysis moments.